The case for Bi-directional charging of electric vehicles in low voltage distribution networks. (1st February 2020) - Crozier, Constance; Morstyn, Thomas; Deakin, Matthew; McCulloch, Malcolm
Highlights: V2G can reduce peak demand up to 40% further than unidirectional smart charging. Both charging losses and resistive network losses increase as a result. The benefit of V2G is largest when around 20% of households on a network have an EV. Solar generation on the network significantly increases its value. Abstract: In recent years, there has been growing interest in AC vehicle-to-grid charging in residential networks. Bi-directional smart charging offers additional flexibility compared to uni-directional smart chargers, but are expensive to install and implement. This paper investigates the costs and benefits to the distribution network that bi-directional charging provides, relative to uni-directional charging. Benefit is quantified in terms of the reduction in the peak demand of the network, and costs are quantified with the increase in throughput of the vehicles' batteries and the increase in electrical losses in the system. Measured data and representative networks are used to construct two representative case studies of residential charging, one in the UK and one in Texas, US.